GREMLIN 2 mutations and dental anomalies - P. N. Kantaputra (2018)
© International & American Associations for Dental Research 2015. Isolated or nonsyndromic tooth agenesis or hypodontia is the most common human malformation. It has been associated with mutations in MSX1, PAX9, EDA, AXIN2, EDAR, EDARADD, and WNT10A. GREMLIN 2 (GREM2) is a strong bone morphogenetic protein (BMP) antagonist that is known to regulate BMPs in embryogenesis and tissue development. Bmp4 has been shown to have a role in tooth development. Grem2 -/- mice have small, malformed maxillary and mandibular incisors, indicating that Grem2 has important roles in normal tooth development. Here, we demonstrate for the first time that GREM2 mutations are associated with human malformations, which include isolated tooth agenesis, microdontia, short tooth roots, taurodontism, sparse and slow-growing hair, and dry and itchy skin. We sequenced WNT10A, WNT10B, MSX1, EDA, EDAR, EDARADD, AXIN2, and PAX9 in all 7 patients to rule out the effects of other ectodermal dysplasias and other tooth-related genes and did not find mutations in any of them. GREM2 mutations exhibit variable expressivity even within the same families. The inheritance is autosomal dominant with incomplete penetrance. The expression of Grem2 during the early development of mouse teeth and hair follicles and the evaluation of the likely effects of the mutations on the protein structure substantiate these new findings.